2019
DOI: 10.1016/j.schres.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vascular tortuosity in schizophrenia and bipolar disorder

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 82 publications
(96 reference statements)
0
27
0
3
Order By: Relevance
“…The prevalence of insomnia in the general population ranges between 8-40%, while the 20-30% of the general population has poor sleep [2], and the underlying pathophysiological mechanisms and causal relationships of insomnia with diseases are poorly understood [3]. The retina is a part of the central nervous system (CNS) and perceived as a "window to the brain" [4] in establishing similarities in the physiology and function of the CNS [5]. The retina also contains a circadian rhythm, and several studies have identified that many aspects of retinal physiology and functions are under the control of a retinal circadian system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of insomnia in the general population ranges between 8-40%, while the 20-30% of the general population has poor sleep [2], and the underlying pathophysiological mechanisms and causal relationships of insomnia with diseases are poorly understood [3]. The retina is a part of the central nervous system (CNS) and perceived as a "window to the brain" [4] in establishing similarities in the physiology and function of the CNS [5]. The retina also contains a circadian rhythm, and several studies have identified that many aspects of retinal physiology and functions are under the control of a retinal circadian system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that telepsychiatry and AI can be effectively deployed for automated evaluation, namely imaging and behavior analysis, 47 evaluating biosignals, 48 assessing language use in mental disorders, 49 acoustic analysis, 50 knowledge-based methods, 51 and retinal examination. 52 56 Other potential uses include online information exchange and support services using social media and networking, 57 psychiatric consultation in primary care and emergency rooms, 58 and asynchronous psychotherapy. 59 Home care and related interventions for the geriatric population are also possible using technology.…”
Section: Discussionmentioning
confidence: 99%
“…Technological features include videoconference, telephone, and messaging systems, 61,62 web-based interactions, 63,64 mobile phone technologies, 65 networking via social media and group discussions, 66 simulated people and places, 67 and internet games. 68 The technology aspect of telepsychiatry has been experimented on a small scale in different cultural set- Retinal examination [52][53][54][55][56] Online information exchange and support services 57 Psychiatric consultation in primary care and emergency rooms 58 Asynchronous psychotherapy 59 Home care and related interventions 60 for ways to accommodate this online health-seeking behavior of their patients in their regular practice, beginning from the current pandemic, into the future.…”
Section: Technological Attributes Of Telepsychiatry and Aimentioning
confidence: 99%
“…After an initial study regarding retinal vascular photography in adolescents with bipolar disorder, 215 there have since been several studies on this topic in adults 216‐219 . One study found that both adults with bipolar disorder and those with schizophrenia had narrower arterioles and wider venules as compared to healthy volunteers, and adults with bipolar disorder had narrower arterioles and wider venues even as compared to adults with schizophrenia, 216 a pattern generally considered indicative of increased cardiovascular risk 220 …”
Section: Vascular Imaging and Functionmentioning
confidence: 99%